Analysis of the Use of Education Funds - Masrupah, Masrupah; Ulfah, Maria; Astriani, Nuraini (Jurnal Ilmiah Mandala Education (JIME), 2024)
Educational activities require financing to support various activities so that educational goals can be achieved. Education financing is not only concerned with how education is financed. It also concerns how the available funds are allocated. The use of education funds requires analysis to see financing achievements and financing efficiency. Thus, an analysis of education costs is needed in an institution to see whether education financing in that institution can realize the institution's goals. In the context of educational institutions, analysis of the use of education costs is related to budgeting in the institution. This research aims to explain the analysis of the use of education funds. The method used in this research uses literature study techniques/literature methods from various existing sources where the researcher provides an explanation of the Analysis of the Use of Education Funds.